2015
DOI: 10.1080/10410236.2014.948709
|View full text |Cite
|
Sign up to set email alerts
|

When parents talk about college drinking: an examination of content, frequency, and associations with students’ dangerous drinking

Abstract: This project examines alcohol messages exchanged between college students and their parents, as well as how such messages associate with college students' dangerous drinking. Undergraduate students ages 18 to 25 years were recruited for the study and asked to recruit a parent. The sample included 198 students and 188 parents, all of whom completed an online survey. This study found parents tended to emphasize the negative aspects of drinking, particularly the dangers of drinking and driving and the academic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Contributing to the family communication literature and providing useful information about parenting practices that might serve to protect youth from SUD, Jackson and Dickson (2011) found that youth have significantly lower rates of smoking intention and initiation when parents engage in antismoking socialization, even if parents currently smoked. Similarly, Menegatos, Lederman, and Floyd (2016) discovered that parent-youth conversations about alcohol use rules had a significant, negative association with students' alcohol consumption; however, they also discovered that if parents focused too much on the negative aspects of alcohol use this could have a boomerang effect, leading to an increase in students' dangerous drinking.…”
Section: Family Communication and Substance Use Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contributing to the family communication literature and providing useful information about parenting practices that might serve to protect youth from SUD, Jackson and Dickson (2011) found that youth have significantly lower rates of smoking intention and initiation when parents engage in antismoking socialization, even if parents currently smoked. Similarly, Menegatos, Lederman, and Floyd (2016) discovered that parent-youth conversations about alcohol use rules had a significant, negative association with students' alcohol consumption; however, they also discovered that if parents focused too much on the negative aspects of alcohol use this could have a boomerang effect, leading to an increase in students' dangerous drinking.…”
Section: Family Communication and Substance Use Preventionmentioning
confidence: 99%
“…By life-span approach, we refer to two areas: (a) human development (early childhood to older adulthood), as well as (b) substance-use development (early experimentation to later misuse). From a human development standpoint, much of family communication research on SUDs focuses on early adolescents (e.g., Ebersole et al, 2014;Miller-Day & Kam, 2010;Reimuller et al, 2011) or young adults (e.g., Menegatos et al, 2016;MillerDay & Dodd, 2004). Concentrating on these particular developmental periods is crucial, given the evidence that suggests anti-substance-use socialization at an early age might be more successful in preventing future SUDs than starting at a later age (Hopfer et al, 2010) and the prevalence of substance use in young adulthood (Glowacki, 2017;Middleton et al, 2017).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Past research suggests that HR messages are among the most common forms of communication that parents use to address alcohol use among college students (Abar et al, 2012). While there are a small number of quantitative studies that have assessed whether parents talk about a limited range of specific PBS (e.g., Donovan et al, 2012;Menegatos et al, 2016), the current study adds to the literature by using a mixed method approach to more broadly understand the content of advice on how to drink safely and the perceived usefulness of that advice from the perspective of college students. The current study extends past qualitative work on family communication about substance use by specifically exploring advice that college students recall getting from their mothers about alcohol use during emerging adulthood, a developmental period when parents may struggle to balance fostering independence while also helping their child to make good decisions around alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Other research uses measures that only examine a couple of specific PBS (Abar et al, 2012). Further, past studies have not specifically explored the HR content separately when using a more comprehensive list of PBS as part of general measures of alcohol communication (Menegatos et al, 2016). In order to better understand the nature and influence of perceived mother-child HR communication, more research is needed about college students' perceptions of the content of parents' advice about drinking safely.…”
mentioning
confidence: 99%
“…The current study examines the longitudinal relationships among maternal disclosure, maternal modeling, and college student alcohol outcomes. While previous research has focused on parental communication in broad terms, there is growing recognition of the need to explore how different types of parent communication are related to child outcomes (Ennett et al, 2001; Kam et al, 2017; Menegatos et al, 2016). Parental disclosure of their own alcohol use is one area that has received relatively little attention, with past studies (Handley & Chassin, 2013; Kam et al, 2017; Kam & Middleton, 2013) finding mixed results about the role of disclosure.…”
Section: Discussionmentioning
confidence: 99%